2021
DOI: 10.1111/nph.17766
|View full text |Cite
|
Sign up to set email alerts
|

A dated phylogeny shows Plio‐Pleistocene climates spurred evolution of antibrowsing defences in the New Zealand flora

Abstract: Some plant traits may be legacies of coevolution with extinct megafauna. One example is the convergent evolution of 'divaricate' cage architectures in many New Zealand lineages, interpreted as a response to recently extinct flightless avian browsers whose ancestors arrived during the Paleogene period. Although experiments have confirmed that divaricate habit deters extant browsers, its abundance on frosty, droughty sites appears consistent with an earlier interpretation as a response to cold, dry Plio-Pleistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“… 2019 ), Neomytus pedunculata MW214671.1 (Maurin et al. 2022 ), Corymbia gummifera KC180800.1 (Bayly et al. 2013 ), Angophora costata KC180805.1 (Bayly et al.…”
Section: Methodsmentioning
confidence: 99%
“… 2019 ), Neomytus pedunculata MW214671.1 (Maurin et al. 2022 ), Corymbia gummifera KC180800.1 (Bayly et al. 2013 ), Angophora costata KC180805.1 (Bayly et al.…”
Section: Methodsmentioning
confidence: 99%
“…This is not surprising given that previous studies testing the efficacy of Bayesian vs. non-Bayesian dating methods have shown that treePL typically overestimates the ages and has narrower confidence intervals than RelTime (Costa et al, 2022). Even so, treePL is still being used with larger datasets (i.e., Li et al, 2019;Janssens et al, 2020;Maurin et al, 2022) given it is computationally less intense than RelTime and other Bayesian dating methods (Mello et al, 2017;Tao et al, 2020;Barba-Montoya, 2021;Costa et al, 2022).…”
Section: Molecular Clock Datingmentioning
confidence: 96%
“… 53 , Muehlenbeckia Meisn. 54 , and Persicaria chinensis (L.) H. Gross 21 . Furthermore, the GC content of the chloroplast genomes in these six plants is lower than the AT content, which is also observed in other Polygonaceae plants such as Fagopyrum dibotrys (D. Don) Hara 55 and R. japonica 56 .…”
Section: Disscussionmentioning
confidence: 99%